The Effect of Gading Marten as Brand Ambassador of Erigo Brand Image - Panji Rizqullah; Indria Angga Dianita (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
Clothing including the primary needs of everyone with good quality and attractive designs will certainly be in demand by the public. In the industrial revolution 4.0, digital technology is the main capital that is needed by business owners who aim to develop their business. Indonesia has many well-known local products, one of which is in the form of t-shirts. In the business world for a business, companies start to promote their business, there are also businessmen who use the popularity of someone, known as a Brand Ambassador. This research was conducted with the aim of knowing how much influence Gading Marten as a Brand Ambassador has on Erigo's Brand Image. This study uses an independent variable, namely Brand Ambassador with sub-variables Visibility, Credibility, Attraction, and Power. The variables contained are Brand Image with Strength, Favorable, and Uniqueness subvariables. This research was conducted using quantitative methods with descriptive research. The sampling technique used in this study is probability sampling, with simple random sampling technique, and the analysis technique uses normality test, heteroscedasticity test, correlation coefficient test, coefficient of determination, simple linear regression, and hypothesis testing using T test. that Brand Ambassador Gading Marten has an influence on Brand Image Erigo 36.9%, and 63.1% is influenced by other factors not examined in this study.